Greening Indian Financial Markets for Sustainable Development - Pradiptarathi Panda; Latha Chari; Ciorstan Smark (Australasian Accounting, Business and Finance Journal, 2024)
This paper highlights the recent developments in India’s securities markets regulations, instruments, and intermediaries. Further, we focus on the developments in sustainable financial instruments and the ESG frameworks implemented by the Indian securities markets’ regulator. We highlight the unique changes in the Indian securities markets in implementing the fastest settlement cycle to T+0, introducing Zero Coupon and Zero principal bonds, blue, green, and yellow bonds, and setting up an efficient market structure by strengthening the governance system. Researchers will benefit from updating their knowledge of sustainable Indian markets, instruments, and regulations through this article. In short, this article highlights the effort of the Indian securities markets’ regulator-SEBI to create dynamic and well-regulated securities markets in India. The fourth annual international capital markets conference was organized to to the foreground India’s multiple challenges and to encourage policy fdiscussion about the latest developments in the Indian securities market. At the end of this article, we summarise the papers in this special issue. We wish to acknowledge the stakeholders who made the 4th Annual Capital Markets Conference a success.
Keywords: Indian securities markets; sustainable finance; recent developments